Literasi promotional mix pada UKM-UKM di kota Depok, Jawa Barat - A. Bernadin Dwi Mardiatmi; Dahlia Pinem (Penerbit Goodwood, 2020)
Purpose: SME is a business that has very good development potential. SMEs in Cipayung Urban Village, Depok City, West Java have various and high-quality products, but unfortunately amid the Covid-19 pandemic, promotion is hampered. This is due to the lack of partners' knowledge about online promotion by utilizing digital media. The purpose of this community service activity is to provide literacy about the promotional mix through online media which is expected to increase partner income. Method: The method used is educational FGD regarding the promotional mix, training on creating business social media accounts (WhatsApp and Facebook) and marketplace accounts (Tokopedia), as well as promotion strategy assistance. Result: The result of this community service activity is the partners' understanding of the promotional mix has increased. It can be seen from the pretest results with an average value of 5.98, increasing in the post-test results to 6.86. In addition, partners can carry out promotional practices through WhatsApp Status, create a Facebook account and create an Online Store on Tokopedia, then carry out promotions by posting product photos. Conclusion: Mentoring assistance activities can increase partners' knowledge about online marketing and can carry out practices regarding promotion through social media. Keywords: Marketing performance, Literacy promotional mix, SME